Roppongi Crossing : new visions in contemporary Japanese art 2004. - Elliott, David; Hisako, Hara; Mami, Kataoka; Minoru, Hatanaka; Nobuko, Shimuta; Takayo, Iida; Exhibition. Roppongi Crossing : new visions in contemporary Japanese art 2004. Tokyo. Mori Art Museum Tokyo. 2004-02-07. 2004-04-11 (Tokyo : Mori Art Museum Tokyo, 2004)
Aida Makoto ; Akiyama, Sayaka ; Aoki, Ryoko ; Atelier Bow-Wow ; Ban, Shigeru ; Carey, Rupert ; Exonemo ; Fukasawa, Naoto ; Fukui, Atsushi ; Fuzitama ; Hachiya Kazuhiko ; Hanayo ; Hatakeyama, Naoya ; Hoki, Nobuya ; Ikeda, Ken ; Ikunishi, Yasunori ; Imamura, Hajime ; Ishikawa, Raita ; Ito Zon ; Ito, Atsuhiro ; Kakegawa, Yasunori ; Kato, Go ; Kato, Mika ; Kimura, Yuki ; Kinoshita, Susumu ; Kosugi, Takehisa ; Kuwakubo, Ryota ; Mikan ; Minä Perhonen ; Mission Invisible ; Murase, Kyoko ; Murayama, Ruriko ; Nakagawa, Masahiro ; Nakamura, Tetsuya ; Nakanishi, Natsuyuki ; Namaiki ; Nibroll ; Nishio, Yasuyuki ; Odani, Motohiko ; Oki, Hiroyuki ; Onodera, Yuki ; Oua ; Pol, Malo ; Sasaguchi, Kazz ; Shibuya, Kiyomichi ; Shimizu, Jio ; Shinoda Taro ; Takahashi, Tomoko ; Takamine, Tadasu ; Takehiko, Sanada ; Takemura, Nobukazu ; Tanaka, Katsuki ; Tanaka, Koki ; Tokyo Picnic Club ; Uemura, Lyota ; Watanabe, Chikako ; Watanabe, Go ; Yanagi Miwa ; Yanobe Kenji ; Yasumura, Takashi
geselect. biog. & bibliog. p. 281-337
Engels
Japans
boek
Keywords: Japan